Conídios e blastosporos de Metarhizium spp. e Beauveria bassiana: virulência para Rhipicephalus microplus e resposta ao calor e à radiação UV-B - Bernardo, Cíntia das Chagas (2016)
The current study compared the virulence of conidia and blastospores of Metarhizium anisopliae s.l. (IP 363), Metarhizium robertsii (IP 146) and Beauveria bassiana s.l. (IP 361 and GC 307) against Rhipicephalus microplus, and the tolerance to heat and UV-B radiation; in addition, it evaluated the development of conidia and blastospores of the isolates IP 146 and IP 361 on the tick cuticle by scanning electron microscopy (SEM). Larvae and engorged females of R. microplus were treated (larvae: 106, 107 or 108 propagules/mL, females: 107 propagules/mL) by immersion in conidia or blastospores suspensions of tested isolates. The higher percentage of larval mortality was obtained in the group treated with conidia of IP 361, which had lower LC50. In bioassays with engorged females, IP 146 and IP 361 blastospores, provided tick percent control superior to 90%, while conidia of the same isolates, promoted 70.97% and 63.29% of tick control, respectively. Ticks were treated topically with 50 μL of fungal suspension (107 propagules/mL) and incubated at different times from 0 to 96 hours to analyze its development on the engorged females cuticle; after each incubation time, the females were fixed and analyzed by SEM. Blastospores of both isolates have started development 4 hours after treatment, demonstrating rapid development and suggesting penetration by the tick natural openings; at 4 hours incubation, indicative of penetration of IP 361 blastospores through the cuticle was observed, but no signs of penetration was observed with IP 146 blastospores at any time evaluated. Furthermore, fungal suspensions (103 propagules/mL) were exposed to heat (45 °C) for several time periods, then inoculated in Petri plates with BDAY medium plus chloramphenicol (0.055% v/v), and incubated for 7 days at 27 °C and RH ≥ 80%. ARSEF 324 conidia (79.1%) were more tolerant to heat than conidia of IP 363 (55.5%), IP 146 (1.5%), GC 307 (0%), and IP 361 (0% ) at 2 hours exposure, as well as blastospores after 60 minutes exposure, demonstrating mean percent CFU of 100%, 12.3%, 30.7%, 55% and 0%, respectively. Fungal suspensions (103 propagules/mL) were also inoculated on BDAY in Petri plates, and exposed to UV-B radiation; after treatment, plates were incubated for 7 days at 27 °C and RH ≥ 80%. No difference in mean relative percent CFU between conidia and blastospores was observed. Suitable adjuvants which aim at protecting fungal propagules against stressful abiotic factors are required for conidia and blastospores; however, the selection of isolates with marked natural tolerance to heat and UV-B radiation may increase performance of bioproducts. Accordingly, it is suggested that blastospores are promising fungal propagules for biological control of ticks, since they were virulent against R. microplus; in addition, the rapid development of blastospores on the tick cuticle indicates they may be exposed shortly to harmful environmental abiotic factors.